Heat shock transcription factor 2 reduces mitochondrial pathway apoptosis in intestinal epithelial cells by inhibiting the increase in mitochondrial membrane permeability in ulcerative colitis - Wen Wang; Yunling Wen; Juan Luo; YingLei Miao; Fengrui Zhang; Junkun Niu (PLoS ONE, 2025)
The destruction of intestinal mucosal mechanical barrier homeostasis caused by excessive apoptosis of intestinal epithelial cells (IECs) is an important reason for the occurrence and development of ulcerative colitis (UC). The increase in mitochondrial membrane permeability caused by the opening of the mitochondrial membrane permeability transition pore (mPTP) is a key link in the initiation of mitochondrial pathway apoptosis. Our previous studies revealed that heat shock transcription factor 2 (HSF2), which is highly expressed in the intestinal mucosa of UC patients, can inhibit the expression of the cytochrome C (Cyto-C)/Caspase-9/Caspase-3 proteins in the mitochondrial pathway of apoptosis, but the regulatory mechanism is unknown. It has been reported that heat shock proteins regulated by heat shock transcription factors are closely related to mPTP opening. Therefore, we hypothesized that HSF2 affects mitochondrial pathway apoptosis in IECs by regulating mPTP opening. In this study, we altered the level of HSF2 in Caco-2 cells by lentivirus transfection to explore the changes in the mitochondrial membrane permeability of Caco-2 cells in an inflammatory environment. Subsequently, the mPTP agonist atractylorhizin (Atr) and inhibitor cyclosporine A (CsA) were used to clarify the regulatory effects of HSF2 on mPTP and the Cyto-C/Caspase-9/Caspase-3 pathways. Our study confirmed for the first time that HSF2 plays a protective role in UC by inhibiting mPTP opening, the increase in mitochondrial membrane permeability and the activation of the mitochondrial-mediated apoptosis pathway in IECs.